Influence of MII/MIII ratio in surface-charging behavior of Zn-Al layered double hydroxides - Rojas Delgado, Ricardo (2008)
Zn-Al layered double hydroxides with different MII/MIII ratios were synthesized by the coprecipitation method and the obtained solids were characterized by powder X-ray diffraction, infrared spectroscopy, acid-base potentiometric titrations, electrophoretic mobility and modeling of the electrical double layer. As general behavior, increasing hydroxyl adsorption with increasing pH and decreasing supporting electrolyte concentration takes place between pH 7 and 12. The electrophoretic mobility of the samples are in all cases positive and it decreases when the pH becomes higher than 9. A net positive charge of the particles, with a point of zero charge (PZC) around 11.8, is deduced from electrophoretic data. A modified MUSIC model, where OH-/Cl- exchange at structural sites and proton desorption from surface hydroxyl groups are taken into account, is used to estimate the deprotonation constants, the number of surface groups, the number of sites with structural charges an the affinity constants for Cl- and OH- of the samples with different MII/MIII ratios. The modeling of potentiometric titrations and electrophoresis data indicates that anions between the layers and negatively charged groups in the particle surface balance most of the structural charge at the particles surface. It shows an important variation of the number of structural sites with the MII/MIII ratio and an important role of surface protonation-deprotonation sites to the electrical behavior and exchange properties of LDHs. © 2007 Elsevier B.V. All rights reserved.